Patient Attitudes Toward Substance Use Screening and Discussion in Primary Care: Comparison Across Demographic Characteristics - Madeline C. Frost; Jennifer McNeely; Noa Appleton; Sarah Farkas; Sarah E. Wakeman; Timothy E. Wilens; Joseph Kannry; Bethany McLeman; Noah Nesin; Richard N. Rosenthal; Carmen Rosa; Aimee Wahle; et al. (Journal of Primary Care & Community Health)
Introduction: Screening for unhealthy alcohol and drug use is recommended in primary care, and effective implementation requires understanding patients’ perspectives. Failure to identify and address potential differences in attitudes toward screening across demographic groups may result in care gaps, but research examining this is limited. Methods: We surveyed 977 adult patients in 9 primary care clinics that participated in a screening implementation study. The survey collected demographics and attitudes toward screening/discussion of alcohol/drug use in primary care. We described responses overall and compared across age, gender, race, and ethnicity using Chi-square/Fisher’s exact tests. Results: Mean age was 51.1 years, and the sample was 39% male, 61% female, 72% White non-Hispanic, 11% Hispanic, 10% Black non-Hispanic, and 6% other/unknown race non-Hispanic. Most participants across all demographic groups reported supportive attitudes. Comfort reporting drug use was lower among young, male, Black non-Hispanic, and Hispanic patients, and comfort with screening overall was lower among middle-aged, Black non-Hispanic, and Hispanic patients. Conclusions: Results suggest that screening/discussion of alcohol/drug use in primary care is generally highly acceptable to patients across demographic groups. Strategies are needed to increase comfort and alleviate concerns about how medical information will be used, particularly among middle-aged, Black, and Hispanic patients.